How can the “resource curse” be broken? Transition factor flows, the urban life cycle and value chain upgrades in resource-based cities - Shuo Lu; Jiaming Li; Wenzhong Zhang; Fan Xiao (Humanities & Social Sciences Communications)
Abstract Resource-based cities (RBCs) face persistent challenges from the “resource curse,” making industrial transition imperative for sustainable development. While the necessity of this transition is clear, the optimal pathways for implementation remain debated. This study investigates how external factor flows drive national value chain (NVC) upgrading in RBCs across different development stages. This study uses a city-level multiregional input-output table and a dynamic panel model to analyse how technology, capital, and labor flows affect the NVC positions of resource- and nonresource-based sectors across 80 Chinese RBCs. Our findings reveal that external technology and capital inflows enhance overall NVC positions, with capital specifically boosting resource-based sectors and both factors elevating nonresource-based sectors. The effectiveness of these factors varies significantly across urban development periods: during the growth period, capital and skilled labor drive respective upgrades in resource- and nonresource-based sectors. During the maturity period, technology inhibits the upgrading, with capital only restraining the upgrading of nonresource-based sectors and skilled labor upgrading nonresource-based sectors. During the depletion period, only capital drives the upgrading of resource-based sectors. In the regeneration period, technology drives the upgrading of both resource- and nonresource-based sectors, whereas capital and skilled labor drive the upgrading of nonresource- and resource-based sectors, respectively. These findings offer strategic guidance for RBC policymakers to align external engagement strategies with specific development stages, advancing sustainable development goals.